Biogeochemistry and hydrography in the eastern subtropical North Atlantic gyre. Results from the European time-series station ESTOC - Neuer, Susanne; Cianca, Andres; Helmke, Peer; Freudenthal, Tim; Davenport, Robert; Meggers, Helge; Knoll, Michaela; Santana-Casiano, J. Magdalena; González-Davila, Melchor; Rueda, Maria José; Llinás Gonzalez, Octavio (Progress in Oceanography, 2007)
Basin wide modeling studies have revealed a clear asymmetry of the biogeochemistry across the subtropical North Atlantic gyre, mainly relating to the magnitude and processes of nutrient supply and new and export production. Time-series measurements of the actual biogeography are needed to confirm and understand the inherent asymmetry. Here we present the first comprehensive time-series measurements carried out in the eastern boundary system of the subtropical North Atlantic gyre at the European Station for Time-Series in the Ocean, Canary Islands (ESTOC), located 100 km north of the Canary Islands. Standard water column properties have been measured at the station since 1994 at monthly intervals; monthly measurements of were added in 1996. There was a clear seasonality in phytoplankton development, with winter maxima of surface chlorophyll of around 0.4 mg Chlorophyll m−3, coinciding with the time of deepest winter mixing. The interannual variability in primary production, new production and net community production was mainly influenced by the onset and depth of wintertime mixing, relative to the depth of the nitracline in a given year. Yearly primary production estimated from in situ chlorophyll a and applying a bio-optical model varied from about 11 to 14 mol C m−2 yr−1. Net community production (NCP) estimated by the net change of dissolved inorganic carbon due to biological processes was always positive, contradicting earlier notions of a heterotrophic subtropical NE Atlantic, and ranged from 2 to 5 mol C m−2 yr−1. New production (NP), estimated as the potential phytoplankton production fuelled by the available nitrate in the euphotic zone due to wintertime convection and mesoscale uplift, ranged from 0.7 to 2.6 mol C m−2 yr−1. The discrepancy between NCP and NP is indicative of carbon-overconsumption in the mixed layer. Particulate organic carbon (POC) flux measured with shallow, moored, time-series traps, and in some years with surface tethered traps, amounted to about 0.2 mol C m−2 yr−1 at 150 m, on ...